2022
DOI: 10.1021/acscatal.2c02433
|View full text |Cite
|
Sign up to set email alerts
|

Carboxamide-Directed Stereospecific Couplings of Chiral Tertiary Alkyl Halides with Terminal Alkynes

Abstract: Herein, we report the stereospecific Sonogashira coupling of a chiral α-bromocarboxamide possessing a tert-alkyl moiety and an alkyne; this reaction produces a chiral tert-alkylated alkyne in a stereoretentive manner. In this reaction, both the CuBr/bathophen catalyst system and carboxamide directing group are essential for achieving the high enantiospecificities of the couplings. Mechanistic studies of this reaction revealed that the alkynyl copper species is the key intermediate that coordinates to the carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…We have investigated several reaction mechanisms including those for similar reaction systems using the B3PW91 functional and have obtained good results. [28][29][30] Vibrational analyses were performed for the optimized structures to calculate their free energies (DG gas ) under the conditions of 1.0 atm and 298.15 K and to confirm the absence or presence of only one imaginary frequency. IRC calculations 13 were performed to confirm that the optimized TSs connect styrene with styrene oxide, as the reactant and the product.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…We have investigated several reaction mechanisms including those for similar reaction systems using the B3PW91 functional and have obtained good results. [28][29][30] Vibrational analyses were performed for the optimized structures to calculate their free energies (DG gas ) under the conditions of 1.0 atm and 298.15 K and to confirm the absence or presence of only one imaginary frequency. IRC calculations 13 were performed to confirm that the optimized TSs connect styrene with styrene oxide, as the reactant and the product.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…In 2022, Nishikata and co-workers reported the stereospecific Sonogashira coupling of a chiral α-bromocarboxamide possessing a tert -alkyl moiety and a terminal alkyne; this reaction produces a chiral tert -alkylated alkyne in a stereoretentive manner (Scheme 25 ). 32 Both the CuBr/bathophen (4,7-diphenyl-1,10-phenanthroline) catalyst system and carboxamide directing group are essential for achieving the high enantiospecificities of the couplings. Mechanistic studies of this reaction revealed that the Cu-alkynyl species is the key intermediate that coordinates to the carboxamide group of chiral α-bromocarboxamide.…”
Section: Copper-catalyzed Sonogashira Cross-coupling Of Alkyl Electro...mentioning
confidence: 99%
“…Our group reported the stereospecific etherifications (via ionic processes) [12] and alkynylations (via Cu I ‐catalyzed radical processes) [13] of α‐bromocarboxamides possessing tert‐ carbon stereocenter. Unfortunately, our reaction methodology proved unsuitable for stereospecific fluorination at tert ‐carbon stereocenter using an inexpensive alkali metal fluoride, [14] which is mechanistically difficult owing to steric hindrance associated with the tert ‐alkyl electrophile and the low nucleophilicity of fluoride.…”
Section: Introductionmentioning
confidence: 99%